STRUCTURAL INVESTIGATION OF SOME NATIVE BIODEGRADABLE PACKAGING MATERIALS - COZAR, Onuc; CIOICA, Nicolae; NAGY, Elena Mihaela; COŢA, Constantin; FECHETE, Radu; FILIP, Claudiu (Studia Universitatis Babeș-Bolyai Ambientum, 2017)
The IR, Raman and NMR methods are used to investigate the structural effects of water and glycerol (plasticizers) on biodegradable packaging materials proceeding from native corn starch. The IR and Raman methods not give a clear response on the amorphous/crystalline content in the investigated starch samples because the origin of vibrational bands is in the same atomic groups of the major starch components (amylose, amylopectin). The nuclear magnetic relaxation data show that the amorphous/crystalline ratio depends not only by the amylose/amylopectin content but also of the mobility and the place of theirs polymer chain segments. The shapes of 13C CP/MAS NMR spectra show clearly the presence of A, B, V-types crystalline structures and also amorphous phase which prevails with the increasing of plasticizers content and also in the extruded starch samples. The composition having starch/glycerol/water 68/17/15 mass % ratio was found to have a dominant amorphous character and very similar features with a commercial specimen (USA) used for the package. It was also found that this best package is extremely degraded after just one day under water absorption.